Pengaruh Teknik Kolase terhadap Kemampuan Motorik Halus Anak pada KelompokB di Gugus VI Kecamatan Buleleng - Purnama, Luh Anggralia; Jampel, I Nyoman; Antara, Putu Aditya (Universitas Pendidikan Ganesha, 2020)
This study aims to determine the effect of the results of fine motor skills of the group of children who were taught using collage techniques. This study is a quasi-experimental study using post-test non-equivalent design only village group control. A total of 18 children from the B3 Kindergarten group Dharma Suda Singaraja were included as the experimental group and 15 children in the B1 group of Kindergarten Aisyiyah Bustanul Athfal were included as a control group. The methods and instruments of data collection used the instrument observation method, observation sheet (check list), then the collected data were analyzed with descriptive statistics and t-test infirential statistics obtained by tcount = 3.15 and ttable = 2.04 at a significance level of 5% with db = 31, by comparing the results of tcount with ttable where tcount> ttable then H0 is rejected and H1 is accepted so that the results of this study find that there is an influence on fine motor abilities of groups of children who are taught collage techniques in Group B children in Cluster VI of Buleleng Subdistrict 2018 / 2019. Thus the collage technique affects the fine motoric abilities of children in group B in Kindergarten Cluster VI of Buleleng Subdistrict.